2019
DOI: 10.1038/s41523-019-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous defeat of MCF7 and MDA-MB-231 resistances by a hypericin PDT–tamoxifen hybrid therapy

Abstract: Currently the greatest challenge in oncology is the lack of homogeneity of the lesions where different cell components respond differently to treatment. There is growing consensus that monotherapies are insufficient to eradicate the disease and there is an unmet need for more potent combinatorial treatments. We have previously shown that hypericin photodynamic therapy (HYP-PDT) triggers electron transport chain (ETC) inhibition in cell mitochondria. We have also shown that tamoxifen (TAM) enhances cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 54 publications
(82 reference statements)
3
47
0
1
Order By: Relevance
“…Our data point out a new “metabolic” function of this NAD + -dependent deacetylase in BC cells, which consists of SIRT6’s ability to enhance PDH expression and activity, OXPHOS, and ATP availability in BC cells. Quite remarkably, SIRT6 overexpression also increased oxygen consumption and ATP synthase activity in MDA-MB-231 cells, which is normally considered to be a glycolysis-dependent cell line, as opposed to other BC cells, which primarily rely on OXPHOS for their metabolism, including MCF7 cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data point out a new “metabolic” function of this NAD + -dependent deacetylase in BC cells, which consists of SIRT6’s ability to enhance PDH expression and activity, OXPHOS, and ATP availability in BC cells. Quite remarkably, SIRT6 overexpression also increased oxygen consumption and ATP synthase activity in MDA-MB-231 cells, which is normally considered to be a glycolysis-dependent cell line, as opposed to other BC cells, which primarily rely on OXPHOS for their metabolism, including MCF7 cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work (13) using a similar naturally occurring perylenequinone PS, hypericin (HYP), we found that HYP‐PDT damages irreversibly complex III of the ETC in DU145, human prostate carcinoma cells. In a more recent publication (14), we further saw that HYP‐PDT caused a profound decrease of both the respiration and the glycolytic rate of MCF7 human breast adenocarcinoma cells, 1 h following irradiation. This is in good agreement with our 2D cerco findings (5), where cerco‐PDT collapsed the respiration and profoundly diminished the glycolytic action in U87, T98G human glioblastoma multiforme and MCF7 human breast carcinoma cells.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, although they are both invasive ductal breast carcinoma cells, they have a number of phenotypic and genotypic differences. MCF-7 are estrogen receptor-positive cells, whereas MDA-MB-231 cells are estrogen and progesterone receptor-negative; in addition, MCF-7 cells express the epithelial phenotype in contrast to the MDA-MB-231 cells that are more mesenchymal (30)(31)(32). Similarly, as shown in Fig.…”
Section: Assessment Of De Genes and Mirnas Related To Emt In Breast mentioning
confidence: 71%